2016
DOI: 10.1098/rsif.2016.0057
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modulation of visual and electrosensory gains for locomotor control

Abstract: Animal nervous systems resolve sensory conflict for the control of movement. For example, the glass knifefish, Eigenmannia virescens, relies on visual and electrosensory feedback as it swims to maintain position within a moving refuge. To study how signals from these two parallel sensory streams are used in refuge tracking, we constructed a novel augmented reality apparatus that enables the independent manipulation of visual and electrosensory cues to freely swimming fish (n ¼ 5). We evaluated the linearity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…This is consistent with studies on mammalian species (such as humans, monkeys and rats) that reveal that sensory inputs are weighted, which often leads to a dominance of certain senses during particular situations and tasks3456. These results are consistent with studies in South American weakly electric fish (Gymnotidae), which also showed a dominance of the electric sense over vision during refuge-tracking and object discrimination3031.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with studies on mammalian species (such as humans, monkeys and rats) that reveal that sensory inputs are weighted, which often leads to a dominance of certain senses during particular situations and tasks3456. These results are consistent with studies in South American weakly electric fish (Gymnotidae), which also showed a dominance of the electric sense over vision during refuge-tracking and object discrimination3031.…”
Section: Discussionsupporting
confidence: 89%
“…The time constant of this decay was similar to the value we obtained by fitting our model. Summation of cues from different modalities has been proposed previously to explain stabilization reflexes [34,35] and forward velocity control [26,36,37] in flies and fish. Summation of visual and odor information has been observed in turning behavior of tethered flies [38], and in the turn probability of freely moving larvae [7].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sensory isolation may not be informative of the sensory dynamics under natural conditions, when a suite of senses participate. Instead, we present conflicting visual and mechanosensory stimuli to dissociate the two modalities while maintaining the sensory pathways intact-similar to human psychophysical experiments in reaching (1) and posture control (6) and experiments in joint visual-electrosensory tracking behaviors in knifefish (7).…”
mentioning
confidence: 99%